An optimal water distribution model for canal systems based on water level - Ke Zhou; Yu Fan; Zhanyi Gao; Mingming Yang; Yifan Wang; Yun Yang (Scientific Reports)
Abstract This paper presents an optimal water distribution model for canals that focuses on canal flow capacity as a foundational premise. The model aims to optimize the flow rate and timing of irrigation to satisfy the water demands necessary for crop growth. Traditionally, the flow rate in the upper-level canal is viewed as the sum of the flow rates in the lower-level canals, with the distribution of water based solely on this flow rate. However, in practice, the upper-level canal must achieve a certain water level to effectively meet the distribution needs of the lower-level canals. Therefore, this study proposes a new approach to water distribution that takes into account the water level of the upper-level canal. We establish an optimal water distribution model for rotational irrigation, as well as a group model for rotational irrigation, utilizing the NSGA-II algorithm to solve these models. The results demonstrate that distributing water to lower-level canals based on the water level of the upper-level canal aligns more closely with actual water distribution scenarios. This paper presents two types of rotational irrigation models: group-based and random water distribution, each tailored for different levels of canals. These models provide valuable references for optimizing water distribution in irrigation districts.